Supervisi Klinis Dengan Pendekatan “Pis” Sebagai Upaya Peningkatan Kualitas Pembelajaran Guru - Abdullah Gasim (Ekspektasi: Jurnal Pendidikan Ekonomi, 2021)
The purpose of this study was to determine the improvement of the quality of teacher learning through clinical supervision with the PIS approach at SD Inpres Loworongga, Ndona Timur District, Ende Regency for the 2018/2019 academic year. The subjects of this study were 8 teachers. The technique of collecting data is through learning activity documents and learning observations (observations) carried out by researchers using clinical supervision instruments, learning implementation plan assessment sheets and learning implementation assessment sheets. The results showed that all teachers were able to prepare the design and implementation well and have well-presented learning documents